Liquidity-to-GDP Ratio, Business Activity, and Financial Security: Implications for Poverty Alleviation - Khan, Wasif Ali; Urooj, Komal; Alamgir, Amina (iRASD Journal of Management, 2024)
Purpose of the research is to find the influence of financial development on poverty in developing economies. Panel data was used of 50 developing countries (1995-2017) and estimated the results by using Generalized Method of Moments (GMM) technique. According to the estimated model, the impact of liquidity-to-GDP ratio (financial development) on poverty was negative, as financial development increases poverty reduces. The outcome variable studied was poverty, which was quantified as the headcount ratio. The other main explanatory variables used to explain or predict poverty were business activity (proxied through economic growth rate) and financial security (proxied through employment). Data was obtained from WDI, Freedom House, and Transparency International. The findings demonstrate a substantial inverse connection amongst liquidity-to-GDP ratio and poverty, implying that enhanced financial systems have the potential to decrease levels of poverty. Furthermore, poverty exhibited negative relationships with business activity and that of with financial security. The results corroborate the assertion that financial development not only promotes economic expansion but also improves poverty alleviation by expanding the availability of financial services for impoverished individuals. Policy recommendations stress the significance of enhancing the financial sector in emerging nations to successfully alleviate poverty.